The influence of safety climate on safety performance in Serdang Hospital - Muthuraman, Sellathurai Pathar (2018)
This aim of the study is to determine the influence of safety climate on safety performance of the healthcare workers in Serdang Hospital. The health services will always be exposed to the risk of accidents or incidents in the workplace. However, safety climate is something fairly new to the healthcare industry. Furthermore, the hospital staff might have different perceptions on safety performance, safety climate and patient safety in response to the type of employer, work environment and regulations. The six dimensions of safety climate in this study are management safety practices, supervisory safety practices, safety attitude, safety training, job safety and co- workers safety practice. To achieve the objectives of the study, a total 150 sets of questionnaires was distributed to the hospital staff concern randomly. Quantitative data was analysed using SPSS software. It includes Descriptive Statistical Analysis, Reliability Test and Pearson Correlation Test. In addition, Multiple regression test was used to test the hypotheses. Meanwhile, all safety climate dimensions have significant relationship with safety performance. Finally, the implication of this study and direction for future research was discussed.